“TRUE” JURISDICTIONAL QUESTIONS AND THE IRRELEVANCE OF A CERTIFICATE OF OUTCOME Bombardier Transportation (Pty) Ltd v Mtiya NO [2010] 8 BLLR 840 (LC) - Avinash Govindjee; Adriaan van der Walt (Obiter, 2021)
In the context of proceedings before the Commission for Conciliation, Mediation and Arbitration (“the CCMA”), the concept of “jurisdiction” generally refers to the authority of the CCMA to conciliate and arbitrate disputes between parties. The CCMA is an independent statutory body established in terms of section 112 of the Labour Relations Act 66 of 1995 (“the LRA”). It does not enjoy the wide powers of inherent jurisdiction and, furthermore, does not derive its jurisdiction from the common law, performing only the functions indicated by labour-related statutes such as the LRA. If there is a dispute about the fairness of a dismissal, or a dispute about an unfair labour practice, the dismissed employee or the employee alleging the unfair labour practice may refer the dispute in writing to the CCMA if no bargaining council has jurisdiction. Such a referral must generally be made within 30 days of the date of a dismissal or within 90 days of the date of the act or omission which allegedly constituted the unfair labour practice. The CCMA must attempt to resolve such a dispute through conciliation. If a commissioner has certified that the dispute remains unresolved, or if 30 days have expired since the CCMA received the referral and the dispute remains unresolved, the CCMA must arbitrate the disputes referred to in section 191(5)(a) upon request. Given the wording of such provisions, it is unsurprising that employers have requested conciliating commissioners to make in limine rulings on matters pertaining to the nature of the dispute (including whether or not the case involves a “dismissal” at all), time limits and applications for condonation and the identity of the parties (in particular, whether the applicant meets the definition of an “employee”). Section 192(1) of the LRA may support the validity of such a request at conciliation. It states that in any proceedings concerning any dismissal, the employee must establish the existence of the dismissal. Such an approach raises a number of questions. For example, are such matters really best dealt with as a point in limine prior to any attempt being made to conciliate the matter, or should they form part of the evidence at arbitration in cases where the dispute could not be conciliated? In addition, what is the effect on jurisdiction of a conciliating commissioner’s certificate of outcome indicating that a dispute remains unresolved? Such matters were raised for adjudication in Bombardier Transportation (Pty) Ltd v Lungile Mtiya NO (Unreported Case No. JR 644/09, Labour Court) (“Bombardier”).